Russia, China and India and the Israel–Palestine Conflict - Rabkin, Yakov M. (Holy Land Studies, 2013)
Outside the Middle East, the future of Israel/Palestine is most often discussed in terms of US foreign policy, where the issue has also acquired religious overtones. This article examines the policies of three nuclear powers – Russia, China and India – on this issue. The analysis takes into account these countries' policies with respect to the entire region, including Iran, in which Russia and the two Asian giants have significant interests. While the three nuclear powers have close contacts with Israel and its military, they opposed Israel's position at the historic UN vote held on 29 November 2012.